Developing Internet interventions to target the individual impact of stigma in health conditions - Neil Thomas; Bronte McLeod; Nev Jones; Jo-Anne Abbott (Internet Interventions, 2015)
A number of health problems are associated with significant stigma, a social phenomenon in which individuals become the object of negative stereotypes. In addition to experiencing negative reactions from others, stigmatised individuals and groups can experience harmful consequences when they internalise these negative prevailing attitudes. The objective of this paper was to consider the potential to develop Internet-based health-related interventions explicitly targeting the effects of stigma on the individual. A review of the literature was conducted to synthesise current conceptualisations of stigma and self-stigma across a number of groups, and to identify current intervention developments. Self-stigma reduction strategies developed for in-person services include cognitive reframing, myth busting, contact with other members of the stigmatised group, and disclosure promotion. The development and provision of interventions targeting self-stigma within an online environment is in its infancy. Our review considers there to be particular potential of online interventions for this target, associated with the capacity of the Internet to promote having contact with peers within one’s stigmatised group, and for user interaction and empowerment. We conclude that self-stigma is a domain in which there is significant potential for innovation with health-related interventions, and provide a number of recommendations for online intervention development.